Rhetorical analysis in scholarly texts: Insights into introduction and literature review patterns - Rochma, Anis Firdatul (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
The rhetorical moves of doctoral students remain underexplored compared to published authors. Addressing this gap offers insights into academic writing development. This study explores rhetorical differences in research article introductions and literature reviews by comparing the strategies of doctoral candidates in linguistics and language education with those of authors in Scopus-indexed journals to highlight their impact on clarity. A mixed-method approach was employed, integrating qualitative analysis using Morley’s (2014) Academic Phrasebank and quantitative data to identify patterns in rhetorical strategies, offering a comprehensive view of writing practices across academic levels. The findings reveal a significant difference in the rhetorical devices used, with Scopus-indexed articles featuring a more complex range of patterns which doctoral students less frequently utilize. These findings underscore the necessity for enhanced academic writing instruction that equips doctoral students with rhetorical strategies. This research provides key insights for academic writing pedagogy, advocating for the integration of targeted approaches such as advanced writing workshops, structured peer review, and the use of rhetorical analysis frameworks to foster the development of writing sophistication and meet publication standards. This research offers valuable insights into academic writing pedagogy, emphasizing the importance of rhetorical sophistication in achieving publication standards.